Role of country governance between sustainable development and firm value in emerging markets - Zeeshan, Ahmed; Yasmeen, Bashir; Bilal, Ahmed; Alvaro, Rocha; Josephine Tan Hwang, Yau (Springer Nature, 2025)
The role of country governance quality between sustainable development performance and firm value in emerging economies is the fundamental objective of this study. The targeted firms are comprised on the firms that have initiated sustainable development practices for public welfare and the data was comprised of 2011–2022. The country level governance plays an indispensable role towards ESG initiatives and firm value in emerging economies. The efficient country governance develops the frameworks which are best suited for the firm in their environmental disclosures and it can increase their value. They can initiate the sustainable development practices for society wellbeing and can create the better image in the market. In this way, the sustainable performance and better firm value can be insured.